Визначення теплоприпливів в кріостат надпровідного обмежувача струму короткого замикання - Данько, Володимир Григорович; Гончаров, Євген Вікторович (НТУ "ХПІ", 2012)
У статті розглянуто теплоприпливи у кріостат обмежувача струму короткого замикання з надпровідною обмоткою. Запропоновано метод розрахунку потужності тепловиділень у кріостаті.

A heat leakage in cryostat of the fault current limiter with a superconducting winding is considered in the article. A technique for computation of thermal emissions in the cryostat is offered.
Heat leacking determination in a cryostat of the superconducting fault current limiter
Keywords: кріостат; обмотка; теплоприлив; струм; fault current limiter; superconducting; heat leakage